Dynamics of Functional States in Shift Personnel at an Oil Exploration Enterprise as Influenced by Workplace Psychosocial Factors - Yana A. Korneeva; Natalya N. Simonova; Anastasiya V. Korneeva; Marina A. Dobrynina (Национальный психологический журнал)
Background. Scientific research provides insufficient information on the influence of psychosocial factors in the workplace of employees at an oil exploration company in the southeast of the Russian Federation on the dynamics in their functional states during the shift period. Objective is to identify and describe the key psychosocial factors at the workplace of the personnel of an oil exploration enterprise in the southeast of the Russian Federation that affect the dynamics of their functional states during the shift period. Study Participants. The study was carried out by means of a scientific expedition in 2022 at one of the sites of an oil exploration enterprise in the Orenburg region. The study involved 58 workers with a 30 days' shift period. Methods. Daily monitoring was carried out in the morning and in the evening of the workers' functional states by objective (variocardiointervalometry, complex visual-motor reaction) and subjective (assessment of the state of reduced performance) methods. The assessment of psychosocial factors in the workplace was carried out using the QPSNordic method. Statistical analysis of the data was carried out using correlation analysis. Results. It has been established that the employees of the oil exploration enterprise during the shift race are characterized by moderate severity of fatigue, monotony, stress and satiety, an acceptable level of general functional state and an average level of efficiency. Psychosocial factors of work requirements, role expectations, control, social support, mastery, teamwork and work motives influence the dynamics of the functional states of workers measured by objective and subjective methods. Factors of social support, management and group work are differentially related to the objective and subjective parameters of the functional states of workers in the dynamics of the shift. Conclusions. Psychosocial factors in the workplace from among role expectations, control, skill, leadership, social support, teamwork and work motives affect the dynamics of the functional states of the personnel of an oil exploration enterprise in the southeast of the Russian Federation during the shift period.